Analisis Peningkatan Kualitas Air Minum Dalam Kemasan Menggunakan Integrasi Six Sigma dan Failure Mode and Effect Analysis - Hakim, M. Hanifuddin; Ramadani, Noviana Rina; Wirakusuma, Kadex Widhy (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2024)
PT. UMSurya Bina Bangsa is a company engaged in the production of Bottled Drinking Water (AMDK). The products produced by PT. UMSurya Bina Bangsa include Suli 5 in 120 ml and 240 ml sizes, as well as S-Five in 330 ml and 600 ml sizes. The issues faced by PT. UMSurya Bina Bangsa include Defects such as dented bottles and broken caps. The aim of this study is to improve the quality of bottled water products. The author of this study uses the integration of Six Sigma and Failure Mode and Effect Analysis (FMEA) methods to improve product quality. Based on the research results, the Root Cause Analysis (RCA) indicates that the majority of product Defects are caused by operator inaccuracy and the use of low-quality materials. Failure Mode and Effect Analysis (FMEA) results show that the highest RPN is caused by the bottle cap pressing process. From the Measure phase, sigma level calculations show a sigma value of 2.10 with a DPMO of 36,041. Improvement recommendations include creating racks for bottle caps to reduce Defects in broken caps, and adding dividers for bottles to prevent crushing while on the conveyor. From the estimated calculations, after implementing the improvement recommendations, the sigma level is expected to increase from 2.10 to 2.54.